Numerical performance assessment of slope reinforcement using a pile-anchor structure under seismic loading - Huang, Yu; Xu, Xi; Mao, Wuwei (Soil dynamics and earthquake engineering (1984), 2020)
The pile-anchor structure is one of the most commonly used and effective methods in slope treatment. However, the dynamic behavior of slope reinforcement using a pile-anchor structure remains poorly understood. Performance assessment of the reinforcement system under seismic loading is therefore critical for reinforcement design. In this study, a numerical model of slope reinforced by pile-anchor structure, together with the analysis procedure, is briefly discussed. We consider four different reinforcement schemes to examine the effectiveness of pile-anchor reinforcement under seismic loading. Finite element analysis is used to derive the dynamic response, and Newmark sliding block analysis is employed to examine the stability of the reinforced slope. The performance assessment results indicate that the pile-anchor structure presents significant advantages of slope deformation reduction with a more reasonable internal force distribution and increased slope stability. •Dynamic finite element analysis is used to simulate the pile-anchor structure.•Dynamic finite element combined with Newmark method is used to evaluate stability.•The dynamic responses of different types of landslide support structures are compared.•Pile-anchor structure presents the significant advantage in enhancing slope stability.